2018
DOI: 10.1097/aln.0000000000002135
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Channel Nav1.3 Is Expressed by Polymorphonuclear Neutrophils during Mouse Heart and Kidney Ischemia In Vivo and Regulates Adhesion, Transmigration, and Chemotaxis of Human and Mouse Neutrophils In Vitro

Abstract: Background Voltage-gated sodium channels generate action potentials in excitable cells, but they have also been attributed noncanonical roles in nonexcitable cells. We hypothesize that voltage-gated sodium channels play a functional role during extravasation of neutrophils. Methods Expression of voltage-gated sodium channels was analyzed by polymerase chain reaction. Distribution of Nav1.3 was determined by immunofluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 55 publications
0
21
0
1
Order By: Relevance
“…This result is in line with several other studies which have investigated the influence of local anesthetics on PMNs. 4,5,27 Migration ceased at concentrations of 1.58 mmol/L and above. Surprisingly in this study, lidocaine at lower concentrations of up to 1.42 mmol/L increased PMN migration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is in line with several other studies which have investigated the influence of local anesthetics on PMNs. 4,5,27 Migration ceased at concentrations of 1.58 mmol/L and above. Surprisingly in this study, lidocaine at lower concentrations of up to 1.42 mmol/L increased PMN migration.…”
Section: Discussionmentioning
confidence: 99%
“…29 Furthermore, higher concentrations of lidocaine led to reduced migration, matching several other studies. [4][5][6]16 Migration stopped at concentrations beyond 1.42 mmol/L. This occurrence may be due to an overwhelming inactivation of the NaV 1.3 channel and the non-canonical effects exerted by local anesthetics, 4,5,7,16 or due to an increase in intracellular calcium concentration, as has been observed in investigations into the effect of LAs on tumor cell lines and muscle cells, [30][31][32] though these investigations require further elucidation.…”
Section: Dovepressmentioning
confidence: 91%
See 1 more Smart Citation
“…Third, recent studies have reported that the voltage-gated sodium channels can comprise a family of nine alpha subunits (referred to as NaV1.1 through NaV1.9), which are variably expressed in leukocytes. A subset of neutrophils recruited to the site of injury has been demonstrated to express NaV1.3 sodium channels 68 , 69 . Na V 1.3 channels can recover from inactivation rapidly and sustain high-frequency firing 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though tetrodotoxin (TTX)-sensitive brain-type sodium channel isoforms Na V 1.1-Na V 1.3 and Na V 1.6 are the main channels expressed in the CNS, their participation in other physiological processes is still under investigation. Recent data provide evidence that Na V 1.1, Na V 1.3, and Na V 1.6 play an important role in action potential propagation in the cardiomyocyte and in excitation-contraction coupling [37,38]. However, further research is needed to verify if the strong toxic effect of the RTX-III toxin comes solely from the modulation of Na V 1.3 channels.…”
Section: Toxicity Of Heteractis Toxinsmentioning
confidence: 99%